2020
DOI: 10.3350/cmh.2020.0152
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and glutamate excretion in alcoholic steatosis: Metabolic synapse between hepatocyte and stellate cell

Abstract: Chronic alcohol consumption induces the development of alcoholic steatosis in the liver, which is one of the most widespread liver diseases worldwide. During general alcohol metabolism, hepatocytes generate mitochondria- and cytochrome P450 2E1 (CYP2E1)-mediated reactive oxygen species (ROS) whose accumulation elicits activation of the hepatic anti-oxidant system, including glutathione (GSH). However, chronic alcohol consumption decreases GSH generation through cysteine deficiency by suppressing the methionine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Human health is strongly related to the homeostasis of gut microflora and the permeability of the intestinal barrier. Over the past few years, many studies have suggested that excessive drinking might cause the disorder of gut microbial homeostasis and the destruction of intestinal barrier permeability, resulting in the proliferation of harmful bacteria in the intestinal tract, the absorption of harmful metabolites, and the damage of liver metabolism function [ 10 , 11 ]. The “gut–liver–metabolite” axis plays an influential role in the pathological development of ALD.…”
Section: Introductionmentioning
confidence: 99%
“…Human health is strongly related to the homeostasis of gut microflora and the permeability of the intestinal barrier. Over the past few years, many studies have suggested that excessive drinking might cause the disorder of gut microbial homeostasis and the destruction of intestinal barrier permeability, resulting in the proliferation of harmful bacteria in the intestinal tract, the absorption of harmful metabolites, and the damage of liver metabolism function [ 10 , 11 ]. The “gut–liver–metabolite” axis plays an influential role in the pathological development of ALD.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, an increasing number of studies have shown that ALD is inextricably linked to the intestinal flora. Alcohol metabolism in the body causes intestinal damage, disrupts intestinal barrier permeability, and produces oxidative-stress-induced damage and inflammation in the intestine [39][40][41][42]. Meanwhile, GOS, a prebiotic, exerts a good effect on regulating and improving the intestinal flora, which has been confirmed in many studies [43][44][45].…”
Section: Discussionmentioning
confidence: 85%
“…Although there have been many efforts to abate these processes, there is still no approved drug for ALD. Since liver damage could not be reversed in the late stage of ALD such as ALC or HCC [ 2 ], there is an urgent need for a new therapeutic agent, especially targeting early-stage ALD. In the present study, we provide several lines of evidence for the efficient preventive effect of Exo-srIκB against ALI, AFL, and ALF in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol-associated liver disease (ALD) caused by chronic and excessive alcohol consumption is one of the most prevalent chronic liver diseases worldwide [ 1 ]. Usually, ALD follows a well-defined disease spectrum starting with the alcohol-associated fatty liver (AFL) that develops into alcohol-associated steatohepatitis, fibrosis (ALF), cirrhosis (ALC), and hepatocellular carcinoma (HCC) [ 2 ]. Chronic alcohol consumption induces gut dysbiosis and increases intestinal permeability, resulting in the hepatic influx of abnormally high amounts of pathogen-associated molecular patterns, including lipopolysaccharide (LPS), through the portal circulation [ 1 ].…”
Section: Introductionmentioning
confidence: 99%